Spatiotemporal Moiré lattice light fields - Yu An-Zhuo; Zhang Wang; Chen Wei; Liu Yuan; Ma Chao-Qun; Yang Jia-Chen; Lu Yan-Qing (Nanophotonics)
Joint space-time modulation of light fields has recently garnered intense attention for enabling precise control over both spatial and temporal characteristics of light, leading to the creation of space-time beams with unique properties, such as diffraction-free propagation and transverse orbital angular momentum. Here, we theoretically propose and experimentally demonstrate spatiotemporal Moiré lattice light fields by controlling the discrete rotational symmetry of a pulse’s spatiotemporal spectrum. Using a 4f pulse shaper and an x − ω modulation strategy, we generate tunable spatiotemporal Moiré patterns with varying sublattice sizes and confirm their diffraction-free behavior in time-averaged intensities. Additionally, we demonstrate spatiotemporal Moiré lattices carrying transverse orbital angular momentum. These findings provide a novel platform for studying spatiotemporal light–matter interactions and may open new possibilities for applications in other wave-based systems, such as acoustics and electron waves.